Cultural diversity and student achievement a basic necessity - Hilliard, Asa; Fifth International Teaching for Intelligence Conference (Washington : SkyLight Professional Development, 1999)
In this candid assessment of why it is important to develop teacher sensitivity to different cultures, Asa Hilliard III examines the role of culture in modifying the mediation of learning
Executive producer, Ela Aktay
Keywords: Multicultural education -- United States -- Curricula; Interdisciplinary approach in education -- United States